Drugs, driving and traffic safety - Verster, Joris C. (Birkhäuser, 2009)
Drugs, Driving and Traffic Safety gives a comprehensive overview of the effects of different medical conditions like neurological disorders, anxiety and depression and their pharmaceutical treatment on driving ability. In addition, the effects of alcohol and drugs of abuse are discussed. Leading experts present the different methodologies to examine effects of drugs on driving, and summarize the recent scientific evidence including epidemiological studies, roadside surveys, laboratory tests, driving simulators, and the standardized driving test. The volume includes guidelines of the International Council on Alcohol, Drugs and Traffic Safety (ICADTS) and the ICADTS Drugs List 2007. Drugs, Driving and Traffic Safety is written for physicians, psychiatrists and pharmacists who want to inform their patients who use psychoactive drugs. Driver health and traffic safety: an overview -- Worldwide trends in alcohol and drug impaired driving -- Drugs, driving, and models to measure driving impairment -- Measurement and methods to determine driving ability -- Simulator studies of drug-induced driving impairment -- The on-the-road driving test -- Epidemiology and traffic safety: culpability studies -- Case-control studies -- Prescribing and dispensing guidelines for medicinal drugs affecting driving performance -- The relationship between drug use and traffic accident severity -- Pharmacokinetics and pharmacodynamics of drugs abused in driving -- The role of driver sleepiness in car crashes: a review of the epidemiological evidence -- Sleepiness, countermeasures and the risk of motor vehicle accidents -- Insomnia, hypnotic drugs and traffic safety -- Drugs, driving and traffic safety in sleep apnea -- Drugs, driving and traffic safety in shift workers -- Effects of anxiolytics on driving -- Antidepressants and traffic safety -- Attention deficit/hyperactivity disorder (ADHD) and driving safety -- Drugs, driving and traffic safety in Parkinson’s disease -- Drugs, driving and traffic safety in multiple sclerosis -- Drugs, driving and traffic safety in acute and chronic pain -- Drugs, driving and traffic safety in allergic rhinitis -- Drugs, driving and traffic safety in diabetes mellitus -- Changes in and predictors of driving after drug use and involvement in traffic crashes because of drugs, 1992–2005 -- Reducing illegal blood alcohol limits for driving: effects on traffic safety -- Interventions to reduce impaired driving and traffic injury -- The alcohol ignition interlock and other technologies for the prediction and control of impaired drivers -- Dose related risk of motor vehicle crashes after cannabis use: an update -- Ecstasy, driving and traffic safety -- Appendix I ICADTS Drug List 2007 -- Appendix II International Council on Alcohol, Drugs and Traffic Safety. Guidelines on experimental studies undertaken to determine a medicinal drug’s effect on driving or skills related to driving.